EMPOWERMENT OF MADRASAH COMMITTEES IN IMPROVING MANAGERIAL PERFORMANCE ISLAMIC JUNIOR HIGH SCHOOL MIFTAHUSSALAM MEDAN - Candra Wijaya; Edi Saputra; Muhammad Sazali (Universitas Dharmawangsa Medan, 2020)
The purpose of this study was to reveal: 1) The recruitment system for members of the madrasah committee at MTs Swasta Miftahussalam Medan; 2) Is the performance of the madrasah committee in accordance with the objectives, roles and functions of the private MTs Miftahussalam Medan; 3) Challenges and obstacles faced by madrasah committees in carrying out their objectives, roles and functions at the Miftahussalam Medan Private MTs; and 4) Efforts to empower madrasah committees in improving madrasah managerial performance in private MTs Miftahussalam Medan.This thesis research uses a qualitative approach with descriptive methods. The collection techniques used interview, observation and documentary studies, while to strengthen the validity of the data findings and the authenticity of the research, the researcher referred to the use of data validity standards consisting of creadibility, transferability, dependability and comfirmability. The results of this study were: 1) Recruitment board k Committee of the m adrasah done by consensus with the madrasas as meeting facilitator. The composition of the madrasah committee committee is a combination of community leaders, ingenious, representatives of parents and other elements of society; 2) The performance shown by the madrasah committee on a general scale has not shown the functions and responsibilities that are expected from its formation in madrasah. The activities shown only revolve around certain activities, such as the realization of the distribution of certain assistance received by madrasah, the rest did not show significant activities for the progress of madrasah. Based on these findings, it is also found that the existence of committees in madrasah has also penetrated into technical matters which are not the responsibility and function of the committee in madrasah; 3) The challenges faced by madrasah committees in carrying out their roles, functions and responsibilities in madrasah are more due to a lack of understanding of their roles, functions and duties as a whole, in addition to the lack of coordination and communication processes between the committee and the madrasah, this situation results in a lack of synergy. and expectations on both sides and tends to generate suspicion, feeling of being watched, and the appearance of being too intrusive; and 4) Efforts to empower madrasah committees, especially in relation to improving madrasah managerial performance, have not progressed as expected or in other words, their empowerment efforts are only temporary in nature. The involvement of the madrasah committee in madrasah managerial activities is only in the areas of madrasah financing and finance as w